American prophecy : race and redemption in American political culture - Shulman, George M. (University of Minnesota Press, 2008)
"Prophecy is the fundamental idiom of American politics - a biblical rhetoric about redeeming the crimes, suffering, and promise of a special people. Yet American prophecy and its great practitioners - from Frederick Douglass and Henry Thoreau to Martin Luther King, James Baldwin, and Toni Morrison - are rarely addressed, let alone analyzed, by political theorists. This paradox is at the heart of American Prophecy, a work in which George Shulman unpacks and critiques the political meaning of American prophetic rhetoric." "In the face of religious fundamentalisms that associate prophecy and redemption with dogmatism and domination, American Prophecy finds connections between prophetic language and democratic politics, particularly racial politics. Exploring how American critics of white supremacy have repeatedly reworked biblical prophecy, Shulman demonstrates how these writers and thinkers have transformed prophecy into a political language and given redemption a political meaning." "To examine how antiracism is linked to prophecy as a vernacular idiom is to rethink political theology, recast democratic theory, and reassess the bearing of religion on American political culture. Still, prophetic language is not always liberatory, and American Prophecy maintains a critical dispassion about a rhetoric that is both prevalent and problematic."--Jacket.